Longitudinal associations of plasma kynurenines and ratios with anxiety and depression scores in colorectal cancer survivors up to 12 months post-treatment - Holthuijsen, Daniëlle; van Roekel, Eline H.; Bours, Martijn J. L.; Ueland, Per M.; Breukink, Stéphanie O.; Janssen-Heijnen, Maryska L. G.; Keulen, Eric T. P.; Gigić, Biljana; Gsur, Andrea; Meyer, Klaus; Ose, Jennifer; Ulvik, Arve; et al. (Psychoneuroendocrinology, 2024)
Introduction - Colorectal cancer (CRC) survivors often experience neuropsychological symptoms, including anxiety and depression. Mounting evidence suggests a role for the kynurenine pathway in these symptoms due to potential neuroprotective and neurotoxic roles of involved metabolites. However, evidence remains inconclusive and insufficient in cancer survivors. Thus, we aimed to explore longitudinal associations of plasma tryptophan, kynurenines, and their established ratios with anxiety and depression in CRC survivors up to 12 months post-treatment. - Methods - In 249 stage I-III CRC survivors, blood samples were collected at 6 weeks, 6 months, and 12 months post-treatment to analyze plasma concentrations of tryptophan and kynurenines using liquid-chromatography tandem-mass spectrometry (LC/MS-MS). At the same timepoints, anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS). Confounder-adjusted linear mixed models were used to analyze longitudinal associations. Sensitivity analyses with false discovery rate (FDR) correction were conducted to adjust for multiple testing. - Results - Higher plasma tryptophan concentrations were associated with lower depression scores (β as change in depression score per 1 SD increase in the ln-transformed kynurenine concentration: −0.31; 95%CI: −0.56,−0.05), and higher plasma 3-hydroxyanthranilic acid concentrations with lower anxiety scores (−0.26; −0.52,−0.01). A higher 3-hydroxykynurenine ratio (HKr; the ratio of 3-hydroxykynurenine to the sum of kynurenic acid, xanthurenic acid, anthranilic acid, and 3-hydroxyanthranilic acid) was associated with higher depression scores (0.34; 0.04,0.63) and higher total anxiety and depression scores (0.53; 0.02,1.04). Overall associations appeared to be mainly driven by inter-individual associations, which were statistically significant for tryptophan with depression (−0.60; −1.12,−0.09), xanthurenic acid with total anxiety and depression (−1.04; −1.99,−0.10), anxiety (−0.51; −1.01,−0.01), and depression (−0.56; −1.08,−0.05), and kynurenic-acid-to-quinolinic-acid ratio with depression (−0.47; −0.93,−0.01). In sensitivity analyses, associations did not remain statistically significant after FDR adjustment. - Conclusion - We observed that plasma concentrations of tryptophan, 3-hydroxyanthranilic acid, xanthurenic acid, 3-hydroxykynurenine ratio, and kynurenic-acid-to-quinolinic-acid ratio tended to be longitudinally associated with anxiety and depression in CRC survivors up to 12 months post-treatment. Future studies are warranted to further elucidate the association of plasma kynurenines with anxiety and depression.